2019
DOI: 10.18585/inabj.v11i1.544
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Media of Human Umbilical Cord Blood Mesenchymal Stem Cell Inhibits Ultraviolet B-induced Apoptosis in Fibroblasts

Abstract: BACKGROUND: Ultraviolet (UV)B irradiated-skin cells may respond either by activating protective or apoptotic mechanisms. Several treatments has been reported to prevent apoptosis of the skin cell. To date, despite of the cell, secretome of mesenchymal stem cell (MSC) has been progressively explored for various treatment. Current research was conducted to find out the possible effect of MSC's secretome to protect normal cells from the UVB irradiation.METHODS: For preparation of the conditioned media human umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…58 UV radiation can also cause increased levels of MMP1 and MMP9, resulting in inhibited synthesis of procollagens and triggering activation of various signaling pathways, namely mitogen activated protein kinase (MAPK), protein activator 1 (AP-1) and nuclear factor kappa B (NF-κB), which contributes to cell damage due to ROS formation and can trigger the apoptosis of skin cells, so as to inhibit skin regeneration and be able to inflict DNA damage in keratinocytes. 24,25,28,29,77 Various studies have been conducted to investigate the effects of secretome as an agent in the fight against photoaging. In vitro testing was done by various methods.…”
Section: Wound Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…58 UV radiation can also cause increased levels of MMP1 and MMP9, resulting in inhibited synthesis of procollagens and triggering activation of various signaling pathways, namely mitogen activated protein kinase (MAPK), protein activator 1 (AP-1) and nuclear factor kappa B (NF-κB), which contributes to cell damage due to ROS formation and can trigger the apoptosis of skin cells, so as to inhibit skin regeneration and be able to inflict DNA damage in keratinocytes. 24,25,28,29,77 Various studies have been conducted to investigate the effects of secretome as an agent in the fight against photoaging. In vitro testing was done by various methods.…”
Section: Wound Healingmentioning
confidence: 99%
“…Methods that were used looked at cell proliferation activity, cellular aging and cellular apoptosis, intracellular ROS levels, and pyrimidine cyclobutane dimer assay (CPD). 26,27,29,58,78 Wang et al reported that there was an increase in cell proliferation from adipose-derived stem cells (ADSC-CM) use, as well as a decrease in the number of cells undergoing apoptosis and a decrease in cellular aging in HDFs. 58 Kim et al also found ADSC-CM can decrease the number of cell deaths from apoptosis (characterized by a decrease in the sub-G1 phase) and increase collagen I synthesis, as well as inhibit the production of MMP1 in HDFs.…”
Section: Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Wound healing is crucial after tooth extraction. Wound healing can be induced with several agents, including cells (2) and their factors (3). In wound healing process, fibroblasts are required as the source of the tissue.…”
Section: Introductionmentioning
confidence: 99%